PRODUCTIVITY ANALYSIS OF PALM SUGAR BUSINESSES IN MONGIILO VILLAGE BULANGO ULU SUBDISTRICT BONE BOLANGO COUNTY - Alex Idrus; Rizal; Sitti Husna N. Djou (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This research aims to find out the productivity of palm sugar businessactors in mongiilo village, this type of research is qualitative research with adescriptive approach that is a problem-solving procedure that is investigatedby making a social reconstruction, and further systematically describes theobject of research. In data collection, researchers consider the selection ofthe first informant to be targeted, namely the palm sugar business itselfwhich is the main key.After doing this research, it is known that, palm sugar business actorsare workers who never know the word tired in doing activities to work aspalm sugar business actors, because in its implementation the palm sugarbusiness actors do work from morning to evening to wait for theirproduction results. The level of productivity depends on traders who buypalm sugar in the market not only that the role of middlemen in the midst ofpalm sugar business actors determines the results of production for theperpetrators